Empowering Educators with AI: A Review of Google's 'Generative AI for Educators' Free Online Course - Koswara, Asep (Yayasan Insan Mulia Bima, 2025)
The Generative AI for Educators training program by Google provides teachers with essential AI tools to enhance instruction, automate administrative tasks, and personalize student learning experiences. This study evaluates the program’s effectiveness by analyzing its content, strengths, and areas for improvement. Findings indicate that the course significantly boosts educators' efficiency, with most participants reporting time savings and increased confidence in using AI. The program’s accessibility ensures that teachers across disciplines can integrate AI without prior technical expertise. However, the study also highlights areas needing enhancement, such as deeper content exploration, interactive elements, and long-term support for participants. Addressing these gaps would maximize the program’s impact and sustainability in educational settings. The study underscores the importance of AI in modern teaching and suggests further research on AI-driven pedagogical strategies. Ultimately, refining AI training programs will empower educators to leverage technology effectively, fostering innovative and student-centered learning environments.